THE PERSPECTIVES OF LOCAL CRAFT WINES IMOLEMENTATION IN RESTARANT BEVERAGE MENU (Development Service Industry Management, 2025)
The article is dedicated to a comprehensive study of the prospects for introducing local craft wines into the beverage menus of modern restaurant establishments. The paper substantiates the relevance of this issue in the context of the development of gastronomic culture in Ukraine, the growing demand for authentic local products, and the formation of a craft trend in the HoReCa sector. The author analyzes the theoretical foundations of forming a wine list as an element of a restaurant's marketing strategy, defining its role in creating a unique concept for the establishment and enhancing the gastronomic experience of guests. Particular attention is paid to the characterization of craft winemaking, its current state, production specifics, and the factors that determine its competitive advantages compared to mass-produced wine.An overview of the historical and socio-cultural prerequisites for the development of craft wineries in Podillia is one of the most promising winemaking regions of Ukraine—is provided. It is shown that Podillia has long-standing traditions of viticulture, which were interrupted and restored due to historical circumstances; however, in the 21st century, they have transformed into an active movement of small wineries. The author analyzes the socio-economic, technological, and regulatory factors that contributed to the emergence of modern Podillia producers, as well as their role in forming a local wine identity. Based on the research results, a systematic characterization of several Podillia wineries is presented, including their varietal portfolios, production specifics, and potential for the restaurant industry. The paper presents a SWOT analysis of craft wines in the context of their inclusion in a restaurant’s wine list, which allowed for the identification of key strengths (authenticity, uniqueness of the offer, storytelling potential), as well as weaknesses and risks (limited production volumes, seasonality, taste instability, low consumer awareness). Attention is focused on the possibilities for deeper interaction between restaurants and local winemakers, the development of tasting practices, gastronomic tourism, and the image advantages that arise from integrating regional wines into the restaurant product. The article also demonstrates pricing models in HoReCa using the example of Podillia craft wines. A differentiated approach to calculating the markup for different consumer segments depending on the establishment's concept (standard, premium, democratic, by-the-glass) is proposed. It is substantiated that pricing is a key component of the successful commercialization of local wines, as it combines economic viability, marketing logic, and the psychological perception of the product by guests. The obtained results can be used as a scientific basis for further research in the field of restaurant management, gastronomic tourism, and craft winemaking.
Keywords: craft; craft winemaking; local wine; restaurant business; beverage menu